Pemasaran Real Estate dengan Web Based Virtual Reality Modelling Language (VRML) - Buyung Yudi Gunawan; Wawan Indarto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
In the concept of marketing known segmentation, targeting and potitioning concept. Al Ries and JackTrour who known as world marketing expert says that “Positioning is what you do to the mind of the prospect.That is, you position your product in the mind of prospect. Now positioning and targeting have been move outfrom mind share to heart share, to get the market share now is not enough only to win the heart of customer ,wehave to subject the customer heart. This moving up change the essence value of the product from content onlychange to context-oriented product. This paper want to make a new way of how to ‘sell’ the product .This papertake study case in information technology as the main point not in marketing studies,this research will developweb based real estate marketing using Virtual Reality Modelling Language Technology (VRML).Kata kunci: VRML, web, marketing.